1996
DOI: 10.1111/j.1360-0443.1996.tb02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, reliability and bias of adolescents' reports of smoking and quitting

Abstract: A follow-up of smoking behaviour to age 18 in a longitudinal study of a birth cohort enabled an assessment of the prevalence of smoking and quitting among adolescents approaching adulthood. There was a dramatic increase in number of daily smokers (15% at age 15 years to 31% at age 18 years), and in a climate of expected decreases in smoking, a history of never smoking to age 15 years was not as protective against future smoking as anticipated. Among 15-year-olds who had experimented with smoking, only 11% per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 22 publications
1
70
0
Order By: Relevance
“…Some limitations of the present study should be mentioned: First, smoking abstinence was not biochemically validated, however, studies among adolescents found self-reported smoking behavior to be reliable and valid [29,30]. Second, the process variables were only assessed retrospectively at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations of the present study should be mentioned: First, smoking abstinence was not biochemically validated, however, studies among adolescents found self-reported smoking behavior to be reliable and valid [29,30]. Second, the process variables were only assessed retrospectively at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…One of the better estimates of self initiated cessation rates comes from a longitudinal study of Australian youth. 5 Researchers interviewed 937 adolescents at age 15 years, and again at age 18. At age 18, only 5.3% of the adolescents who were daily smokers at age 15 were abstinent for the past month at the time of their interview.…”
Section: The Need For Youth Cessation Interventionsmentioning
confidence: 99%
“…Although many adolescent smokers report wanting to quit, few remain abstinent after making a cessation attempt ( Mermelstein, 2003 ;Stanton, McClelland, Elwood, Ferry, & Silva, 1996 ;Zhu, Sun, Billings, Choi, & Malarcher, 1999 ). Even with treatment, the large majority of adolescents relapse back to smoking ( Colby & Gwaltney, 2007 ;Sussman, Sun, & Dent, 2006 ).…”
Section: Introductionmentioning
confidence: 99%